Can we get more out of Net-Promoter Data? - Mecredy, P; Feetham, PM; Wright, MJ (ANZMAC)
Net-Promoter Score (NPS), a loyalty measure, is used extensively in commercial market research due to its simplicity of use and ease of understanding, despite criticism of the metric. Given the widespread use of NPS commercially, it is important to understand whether applying alternative loyalty measures has any advantages over Net-Promoter. This paper aims to demonstrate whether a likelihood mean and Polarization Index, φ, provide different results to Net-Promoter. These three measures were applied to data collected from an on-line survey of 1,818 participants who evaluated brands in a service industry. The findings show that all three measures provided similar variations in loyalty across brands and regions. The likelihood mean and NPS are strongly correlated, indicating that no one measure is more superior to the other at measuring loyalty within a service industry in New Zealand. However, the Polarization Index appears to assess loyalty differently to the likelihood mean and NPS.
Keywords: Net-Promoter, polarization index, brand loyalty measures